MOLECULAR IDENTIFICATION OF SOME SPECIFIC VIRULENCE GENES IN ESCHERICHIA COLI RESPONSIBLE FOR UTIS - Humada, Yasser Hamad (PT. Antis International Publisher, 2025)
Objective: This study aimed to determine the phylogroups and specific virulence genes of uropathogenic Escherichia coli (UPEC) in patients suspected of urinary tract infections (UTIs) at Al-Hawija General Hospital in Kirkuk. Methods: A total of 120 urine samples were collected from patients exhibiting clinical signs of UTIs. The presence of bacteria was confirmed using light microscopy and bacterial cell identification techniques. Positive samples underwent bacterial cultivation and DNA extraction using a specialized kit. Polymerase chain reaction (PCR) analysis was performed to identify virulence factor genes (chuA, fimH, uidA, and arpA) associated with pathogenicity. Results: Of the 120 analyzed samples, 90 (75%) showed bacterial growth, with 25 (27.78%) from males and 65 (72.22%) from females. PCR analysis confirmed the presence of virulence genes in E. coli isolates, linking these genes to the bacteria's role in causing UTIs. Novelty: This study provides a comprehensive analysis of UPEC phylogroups and virulence genes in UTI patients, highlighting gender-based prevalence. The use of PCR to identify pathogenic genes offers valuable insights into the molecular mechanisms of UPEC, which could inform future diagnostic and treatment strategies.